Reproductive biology of Apocryptes bato (Gobiidae) in the Payra River, southern Bangladesh. (29th August 2018) - Ahamed, Ferdous; Saha, Newton; Ahmed, Zoarder F.; Hossain, Md. Yeamin; Ohtomi, Jun
Abstract: The gobioid fish Apocryptes bato (Hamilton, 1822) is a species of mudskipper found in Bangladesh, India, and Myanmar. The reproductive biology of A. bato including sex ratio, size at sexual maturity, breeding season, fecundity, and condition factor was studied in the Payra River, southern Bangladesh during May 2016 to April 2017. A total of 1, 028 specimens (303 males and 725 females) were collected. The overall sex ratio was significantly different from the expected value of 1:1 (male: female = 1:2.39, χ 2  = 173.23, p  < 0.05). Size at sexual maturity was estimated as 4.9 cm standard length. Monthly variations in gonadosomatic index indicate that the main breeding season is from May to December. There was a significant positive correlation of body length and body weight with fecundity. Fulton's condition factor varied in both sexes and was attributed to variations in GSI with maturity. Breeding season was significantly associated with rainfall, but not air temperature. Our findings should improve management and conservation of this fish in the Payra River and surrounding ecosystems.